Politik Hukum Undang-undang Kekuasaan Kehakiman - H.M Hambali (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
The Republic of Indonesia is a unitary state in the form of a republic,sovereignty belongs to the people and the law is not based on power alone. Sovereigntybelongs to the people, the highest authority is the people. To enforce the law, Article 24paragraph (2) of the 1945 Constitution specifies that judicial power exercised by aSupreme Court and judicial bodies underneath it in the public courts, religious courts,military courts, administrative courts, and by a Constitutional Court. Agencies whosefunctions related to the judicial authorities set out in the Act. Act No. 48 of 2009 onJudicial Power, is based on the interests of the people.